Treatment of severe recurrent hepatitis C after liver transplantation in HIV infected patients using sofosbuvir‐based therapy. Issue 12 (21st April 2016) - Campos‐Varela, I.; Moreno, A.; Morbey, A.; Guaraldi, G.; Hasson, H.; Bhamidimarri, K. R.; Castells, L.; Grewal, P.; Baños, I.; Bellot, P.; Brainard, D. M.; McHutchison, J. G.; et al.
Summary: Background: For liver transplant recipients with hepatitis C virus (HCV) and human immunodeficiency virus (HIV) co‐infection, recurrence after LT is associated with a higher risk of graft loss than for HCV mono‐infected patients. Prior HCV treatment options were limited by side effects and drug–drug interactions. Aim: To evaluate treatment outcomes with sofosbuvir (SOF)‐based therapy among HIV/HCV coinfected liver transplant recipients. Methods: Access to SOF and ribavirin (RBV) prior to regulatory approval was attained via an international compassionate access program for transplant recipients with a life expectancy of 1 year or less in the absence of HCV treatment. This report focuses on the short and longer term outcomes in HCV‐HIV co‐infected liver transplant recipients. Results: Twenty patients were treated, nine with early severe recurrence and 11 with cirrhosis. Eleven patients received SOF and RBV, one SOF, RBV and Peg‐interferon, three SOF, RBV and simeprevir and five SOF, RBV and daclatasvir. Of the 18 patients who completed treatment, 16 (89%) achieved sustained virological response 12 weeks after the end of treatment (SVR12). Liver function tests (including bilirubin and albumin) improved significantly over time. Nineteen serious adverse events occurred in eight (40%) patients, none of them related to SOF. Two patients died during treatment and another, 1 year after the end of therapy, due to progressive end‐stage liver disease. Importantly, HIV suppression was not compromised. No significant drug‐drug interactions were reported. Conclusions: Sofosbuvir‐based regimens are safe, well‐tolerated and provide high rates of SVR in HCV‐HIV co‐infected patients with severe recurrence after‐liver transplant.